2014
DOI: 10.5505/tjoncol.2014.1080
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain radiotherapy results of patients with brain metastases and investigation of their prognostic factors

Abstract: OBJECTIVESTo assess the survival ratios of patients with brain metastasis after whole brain radiotherapy according to recursive partitioning analysis (RPA) classification and other prognostic factors. METHODSWhole brain radiotherapy results and prognostic factors of 62 patients with brain metastasis were studied retrospectively. RESULTSThe median survival rate in our study was 6.9 months. Single variation analysis demonstrated statistically significant survival results independently in female patients, with Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Brain metastases are most commonly detected between ages 50 and 70 years (40) . In this study, the mean patient age was 54.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases are most commonly detected between ages 50 and 70 years (40) . In this study, the mean patient age was 54.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, some cases of tumor types such gastro-oesophageal cancers, genitourinary cancers, head and neck cancers and sarcomas are rarely lead to BM. In 2700 cases from the Memorial Sloan-Kettering Cancer Center in New York, Victor et al reported that the distribution of primary cancers was as follows: 48% lung, 15% breast, 9% melanoma, 1% lymphoma, 3% gastrointestinal, 11% genitourinary, 10% osteosarcoma, 5% neuroblastoma and 6% head and neck cancer [11]. The prognosis of patients with brain metastases is generally poor, and survival is about 4 weeks, if untreated [12].…”
Section: Discussionmentioning
confidence: 99%